(2u-5)(2+u)=0

Simple and best practice solution for (2u-5)(2+u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2u-5)(2+u)=0 equation:


Simplifying
(2u + -5)(2 + u) = 0

Reorder the terms:
(-5 + 2u)(2 + u) = 0

Multiply (-5 + 2u) * (2 + u)
(-5(2 + u) + 2u * (2 + u)) = 0
((2 * -5 + u * -5) + 2u * (2 + u)) = 0
((-10 + -5u) + 2u * (2 + u)) = 0
(-10 + -5u + (2 * 2u + u * 2u)) = 0
(-10 + -5u + (4u + 2u2)) = 0

Combine like terms: -5u + 4u = -1u
(-10 + -1u + 2u2) = 0

Solving
-10 + -1u + 2u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(-2 + -1u)(5 + -2u) = 0

Subproblem 1

Set the factor '(-2 + -1u)' equal to zero and attempt to solve: Simplifying -2 + -1u = 0 Solving -2 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1u = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1u = 0 + 2 -1u = 0 + 2 Combine like terms: 0 + 2 = 2 -1u = 2 Divide each side by '-1'. u = -2 Simplifying u = -2

Subproblem 2

Set the factor '(5 + -2u)' equal to zero and attempt to solve: Simplifying 5 + -2u = 0 Solving 5 + -2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2u = 0 + -5 -2u = 0 + -5 Combine like terms: 0 + -5 = -5 -2u = -5 Divide each side by '-2'. u = 2.5 Simplifying u = 2.5

Solution

u = {-2, 2.5}

See similar equations:

| 35m=7m+49 | | 50/100 | | 21x+12x= | | 60/44 | | 6x+31=85 | | -37-9x=67-5x | | 5x^2+6x+2*(x*1)=125 | | 2n^2-n-136=0 | | (h+3)-(8h-1)= | | 2x^2+13x+31=0 | | 2x-5(2)=8 | | 0.75x+1=65 | | 2(-1)-5y=8 | | 18+8x=180 | | 5x*2=0 | | 2x+3y-4-5x+2= | | -3+-5=-8 | | 50x^2+85x+30= | | 5x^2+6x^2+6x=123 | | .9x=13-.18x | | x*(1/10)=2/5 | | 3x-147=56-4x | | 4x+7.2342=-2x | | X=360 | | k+20= | | 3s-6=18 | | 4x+50=-2x | | 4x+7.2=-2x | | 3(3q-2)=2(q+5) | | 3x+153=7x+97 | | 6s-5=0 | | 4x+7.10=-2x |

Equations solver categories